Menanamkan Sikap Toleransi Pada Anak Usia Dini Melalui Pola Pembiasaan (Studi Kasus pada TK Meraih Bintang Pangandaran Jawa Barat) - Ida Kurniasih; Jenal Abidin; Hamidah Hamidah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This study aims to find out how to instill religious tolerance in early childhood in Meraih Bintang Kindergarten through habituation patterns. Through the observation method, it can be concluded that the learning efforts carried out in instilling an attitude of tolerance in early childhood in Meraih Bintang Kindergarten are by using several activities that use habituation patterns. The pattern of habituation is to get children to adapt according to their respective beliefs. Activities carried out with this habituation pattern include morning prayer before learning activities begin according to their respective religions. Then the Friday blessing activities where children learn to get to know their respective religions more deeply, starting from how to worship, commemorate religious holidays and others. In addition, teachers instill an exemplary attitude by always conveying good attitudes and tolerance to children. The importance of early education in instilling tolerance in children, because in the future they will interact directly with various diversity.